Height correlates with dyslipidemia in non-overweight middle-aged Japanese men. Issue 1 (December 2016) - Shimizu, Yuji; Yoshimine, Hiroyuki; Nagayoshi, Mako; Kadota, Koichiro; Takahashi, Kensuke; Izumino, Kiyohiro; Inoue, Kenichiro; Maeda, Takahiro
Abstract Background Our previous study showed that height is inversely associated with the risk of stroke in middle-aged Japanese men, particularly in those with a low body mass index (BMI). Since height is regarded as a surrogate maker of childhood social and physical condition, while BMI may reflect primarily on the current physical condition, a detailed analysis of those with a lower BMI may elucidate the effects of childhood conditions. On the other hand, dyslipidemia is recognized as a prominent risk factor for cardiovascular disease. However, no studies have reported on the association between height and dyslipidemia accounting for BMI status. Methods We conducted a hospital-based general population cross-sectional study of 3016 Japanese men aged 30–59 years. Dyslipidemia is defined by the Japan Atherosclerosis Society (JAS) Guidelines as follows: triglycerides (TG) ≥ 150 mg/dL and/or low-density lipoprotein-cholesterol (LDL) ≥ 140 mg/dL, and/or high-density lipoprotein-cholesterol (HDL) < 40 mg/dL, and/or lipid lowering medication use. Results Independent of classical cardiovascular risk factors, height was found to be inversely associated with dyslipidemia in subjects with a BMI <25 kg/m2 but not in subjects with a BMI ≥25 kg/m2 . Adjusted odds ratios (ORs) and 95% confidence intervals (CIs) of dyslipidemia for an increment of one standard deviation (SD) in height (5.7 cm) were 0.90 (0.82–0.99) for subjects with a BMI < 25 kg/m2 and 1.02 (0.89–1.17) for subjects with a BMI ≥ 25 kg/m2 . Conclusion Height is inversely associated with dyslipidemia in those with a BMI < 25 kg/m2 but not with a BMI ≥ 25 kg/m2 .